Development and use of a research productivity assessment tool for clinicians in low-resource settings in the Pacific Islands: a Delphi study. Issue 1 (December 2016) - Ekeroma, Alec; Shulruf, Boaz; McCowan, Lesley; Hill, Andrew; Kenealy, Tim
Abstract Background Research performance assessments have proliferated, but research indicators for use amongst clinicians in poorly resourced countries have been ill-defined. The aims of the present paper were to determine a set of indicators as determined by clinician participants from the Pacific Islands and a panel of research experts for use in the performance assessment of clinicians. Methods Two focus group discussions, one for nurses and one for doctors, were used to obtain the views of 28 Pacific Island clinicians of the BRRACAP Study about what the research indicators should be. A modified Delphi survey was used to obtain a consensus amongst 19 research experts, with Pacific Island research experience, as to what the indicators should be and then to rank these in terms of importance. A survey of the participants obtained data on the research tasks/actions performed 20 months after the initial research workshop. A resultant tool comprising of 21 indicators was used to assess the performance of 18 Pacific participants. Results The Pacific Island clinicians determined that research was important and that performance should be measured. They identified research indicators that could be used in their settings and ranked their importance using a points system. The panel of experts identified implementation of research findings, collaborations and actual change in practice as more important, with bibliometric measurements low down in the scale. Although only 64 % of the 28 BRRACAP Study participants returned the questionnaire, 39 % of those performed more than half of the 21 indicators used. Of the 18 Pacific clinicians assessed, 7 (39 %) performed 10 or more tasks. Conclusions A research performance assessment tool was developed using process and output indicators identified by Pacific clinicians and a panel of research experts. The tool, which placed emphasis on process and outputs that were not bibliometric based, proved useful in assessing the performance of Pacific clinicians working in a low-resource setting.